2008
DOI: 10.1182/blood-2008-02-139634
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil secretion products pave the way for inflammatory monocytes

Abstract: The leukocyte response in inflammation is characterized by an initial recruitment of polymorphonuclear leukocytes (PMN) preceding a second wave of monocytes to the site of injury or infection. In the mouse, 2 populations of monocytes have been identified, Gr1 ؊ CCR2 ؊ CX3CR1 hi resident monocytes and Gr1 ؉ CCR2 ؉ CX3CR1 lo inflammatory monocytes. Here, intravital microscopy of the musculus cremaster and a subcutaneous air pouch model were used to investigate a possible link between PMN extravasation and the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
348
3
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 369 publications
(368 citation statements)
references
References 57 publications
15
348
3
2
Order By: Relevance
“…A member of the formyl peptide receptor (FPR) family has been identified recently as the receptor for cathepsin G on leukocytes mediating its chemotactic effect [59]. In line with this, it was demonstrated recently that FPR antagonists efficiently block the chemotactic response of inflammatory monocytes to azurocidin in vivo, suggesting that a member of this family is important in mediating azurocidin-dependent chemotaxis [35].…”
Section: Azurocidin Mediates Its Effects On Leukocytes Via ␤ 2 -Integmentioning
confidence: 81%
See 1 more Smart Citation
“…A member of the formyl peptide receptor (FPR) family has been identified recently as the receptor for cathepsin G on leukocytes mediating its chemotactic effect [59]. In line with this, it was demonstrated recently that FPR antagonists efficiently block the chemotactic response of inflammatory monocytes to azurocidin in vivo, suggesting that a member of this family is important in mediating azurocidin-dependent chemotaxis [35].…”
Section: Azurocidin Mediates Its Effects On Leukocytes Via ␤ 2 -Integmentioning
confidence: 81%
“…It was demonstrated recently that azurocidin specifically stimulates efflux of inflammatory monocytes (Fig. 1C) [35]. Murine inflammatory monocytes were defined as CX3CR1 lo CCR2 ϩ GR1 ϩ [36].…”
Section: Azurocidin Induces Recruitment Of Monocytesmentioning
confidence: 95%
“…Masek and Hunter (2013) stated that macrophages can be infected by T. gondii, they are able to limit parasite replication and produce cytokines that contribute to resistance, making them important regulatory and effector cells during toxoplasmosis. Neutrophils influence the T-cell response by enhancing the functions of dendritic cells (van Gisbergen et al, 2005) or inflammatory monocytes (Soehnlein et al, 2008). Infection of mice by intraperitoneal (i.p.)…”
Section: Resultsmentioning
confidence: 99%
“…In the early stages of atherosclerosis the neutrophil plays a key role, through the release of specific chemoattractant mediators, in the consequent recruitment of inflammatory monocytes to the athero-prone site (44,63). Using an acute model of inflammation, we have shown that treatment of ApoE KO mice with inorganic nitrate reduces first neutrophil recruitment, followed by consequent reductions in the number of inflammatory monocytes.…”
Section: (B) the Same Pattern Was Observed In Erythrocytes (G And H)mentioning
confidence: 95%